Comparison of Conventional Open Thyroidectomy and Endoscopic Thyroidectomy via Breast Approach for Papillary Thyroid Carcinoma - Zhuo Tan; JiaLei Gu; QianBo Han; WenDong Wang; KeJing Wang; MingHua Ge; JinBiao Shang (International Journal of Endocrinology)
Purpose. The aim of this study was to evaluate the feasibility of endoscopic thyroidectomy via breast approach for papillary thyroid carcinoma (PTC). Methods. Between March 2008 and March 2013, 34 patients with PTC received endoscopic thyroidectomy (endo group) and 30 patients received conventional open thyroidectomy (open group). Patients in two groups underwent ipsilateral central compartment node dissection. The two groups were compared in terms of patient characteristics, perioperative clinical results, and postoperative complication. Results. The rates of lymph node metastasis in endo group and open group were 23.5% (8/34) and 13.3% (4/30), respectively, without statistically significant difference (P=0.351). The mean number of lymph nodes dissected was 2.4 ± 2.9 in endoscopic group and 2.2 ± 1.9 in open group (P=0.774). During the follow-up period, there was no recurrence or metastatic patients in two groups. All patients received the excellent cosmetic results in endo group, while 25 patients were satisfied with the cosmetic result and 5 were unsatisfied in the open group. Conclusions. The efficacy of endoscopic thyroidectomy via breast approach could be comparable to conventional open thyroidectomy in selected patients with PTC.